HUBUNGAN ANTARA ADEKUASI HEMODIALISA DENGAN KUALITAS HIDUP PASIEN YANG MENJALANI HEMODIALISA DI RSUD KABUPATEN INDRAMAYU - hikmawati, kitri; nur 'aeni, wiwin; salsabillah, salsabillah (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Quality of life assessment is an important indicator for assessing the effectiveness of a given hemodialysis treatment.  Quality of life is associated with mortality and morbidity of chronic renal failure patients.  One of the factors that affect the quality of life of patients undergoing hemodialysis is hemodialysis adequacy. The purpose of this study was to determine the relationship between hemodialysis adequacy and the quality of life of patients undergoing hemodialysis. This study was a quantitative study, with a correlative descriptive method with a cross-sectional approach. The population in this study was all patients undergoing hemodialysis in RSUD Kabupaten Indramayu.  The sample of this study was 52 respondents, which was taken by using purposive sampling techniques.  This study used an instrument Kt/V observation sheet and a WHOQoL-BREF quality of life questionnaire. The results of the study found that 26 (50%) of respondents had adequate hemodialysis adequacy and 29 (55,8%) respondents had a good quality of life.  The results of the bivariate test obtained a P-value of  0.579 (α = 0,1), it is mean that no meaningful relationship between hemodialysis adequacy and the quality of life of patients undergoing hemodialysis in RSUD Kabupaten Indramayu.  The next suggestion for researchers is to examine other factors that affect the quality of life that are more relevant to the kidney failure disease                                                 Keywords : adequacy hemodialysis, hemodialysis, quality of life